The Iodine Rush: Over- or Under-Iodination Risk in the Prophylactic Use of Iodine for Thyroid Blocking in the Event of a Nuclear Disaster - Calcaterra, Valeria; Mameli, Chiara; Rossi, Virginia; Massini, Giulia; Gambino, Mirko; Baldassarre, Paola; Zuccotti, Gianvincenzo (Frontiers in Endocrinology, 2022)
Iodine is an essential element for the production of thyroid hormones (THs). Both deficient and excess iodine intakes may precipitate in adverse thyroidal events. Radioactive iodine (RI) is a common byproduct of nuclear fission processes. During nuclear emergencies RI may be released in a plume, or cloud, contaminating the environment. If inhaled or ingested, it may lead to internal radiation exposure and the uptake of RI mainly by the thyroid gland that absorbs stable iodine (SI) and RI in the same way. A dose of radiation delivered to the thyroid gland is a main risk factor for the thyroid cancer development. The SI prophylaxis helps prevent childhood thyroid cancer. The thyroid gland saturation with prophylactic SI ingestion, reduces the internal exposure of the thyroid by blocking the uptake of RI and inhibiting iodide organification. However, negative impact of inadequate SI intake must be considered. We provide an overview on the recommended iodine intake and the impact of SI and RI on thyroid in children and adolescents, discussing the benefits and adverse effects of the prophylactic SI for thyroid blocking during a nuclear accident. The use of SI for protection against RI may be recommended in cases of radiological or nuclear emergencies, moreover the administration of iodine for prophylactic purposes should be cautious. Benefits and risks should also be considered according to age. Adverse effects from iodine administration cannot be excluded. Precise indications are mandatory to use the iodine for thyroid blocking. Due to this natural adaption mechanism it’s possible to tolerate large doses of iodine without clinical effects, however, a prolonged assumption of the iodine when not needed can be dangerous and may precipitate in severe thyroidal and non-thyroidal negative effects.